IMPLEMENTASI ALGORITMA ZHU TAKAOKA PADA APLIKASI KITAB JURRUMIYYAH BERBASIS ANDROID - Novianti, Nia; Hasibuan, Nelly Astuti; Suginam, Suginam (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Kitab Al-Ajurrumiyah is a book that contains Arabic grammar from the 7th century to the 13th century AD compiled by a Moroccan linguist named Abu Abdillah Sidi Muhammad bin Daud Ash-Shanhaji aka Ibn Ajurrum with the aim of make it easier for students in pesantren and the general public to learn the rules of nahwu. Kitab Al-Ajurrumiyah has very much content and uses the type of writing Arabic so to study the contents of the book Al-Ajurrumiyah is not an easy thing for students and the general public, especially those who still use the printed book Al-Ajurrumiyah. The problem that often occurs with the use of the Al-Ajurrumiyah book in the form of printed books is when searching for the contents of the Al-Ajurrumiyah book because it has to search the contents of the book manually by opening one by one each sheet of the Al-Ajurrumiyah book so that it takes a lot of time to find content. the book that will be studied and requires a large storage area and difficult to carry if traveling so it is necessary to develop a system by designing an Android-based Al-Ajurrumiyah book application that has good search features to minimize the time needed to find the search results in the Al-Ajurrumiyah book will be studied. Based on the description of the problem the author designed the Android-based Kitab Al-Ajurrumiyah application using the Eclipse Juno Software. In this study the author applies the zhu takaoka algorithm to simplify the process of searching for translations of the contents of the Al-Ajurrumiyah verse in the Android-based Al-Ajurrumiyah Kitab Application. The Android-based Al-Ajurrumiyah Book application designed in the research can be operated on smartphones that are ended by an android-based operating system so that the use of this Android-based Kitab Al-Ajurrumiyah application is very easy because it does not have a size too large so it can be used anywhere and anytime.Keywords: Application, Kitab Al-Ajurrumiyah, Android, Eclipse Juno, Zhu Takaoka